Architectural Evolution and Strategic Convergence in Cross-Platform Software Development Frameworks - Joseph M. Kingsley (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
The accelerating diversification of computing platforms, devices, and deployment environments has profoundly reshaped the discipline of software engineering over the past two decades. From desktop-centric paradigms to mobile-first strategies, and from monolithic server-side architectures to distributed cloud-native ecosystems, developers have been compelled to seek frameworks that reconcile performance, maintainability, scalability, and economic feasibility across heterogeneous platforms. Within this context, cross-platform development has emerged not merely as a technical convenience but as a strategic imperative for organizations operating under constraints of time-to-market, resource optimization, and long-term system evolution. This research article undertakes an extensive, theory-driven investigation into the evolution of cross-platform development frameworks, with particular emphasis on web and application ecosystems that bridge server-side, client-side, and mobile environments. The study is grounded in a comprehensive synthesis of prior scholarly work on cross-platform architectures, comparative framework evaluations, and performance considerations, while situating the evolution of ASP.NET to ASP.NET Core as a pivotal case illustrating broader industry trends toward modularity, openness, and platform neutrality (Valiveti, 2025). By treating ASP.NET Core not in isolation but as part of a wider constellation of cross-platform technologies such as React Native, Flutter, Progressive Web Applications, and middleware-driven approaches, this article articulates a unifying analytical lens that integrates architectural theory, historical development, and empirical insights reported in the literature. The discussion extends these findings through critical engagement with competing scholarly perspectives, addressing enduring debates concerning native versus cross-platform development, the limits of write-once-run-anywhere ideals, and the implications of framework evolution for future software engineering education and practice. By foregrounding the evolutionary arc of frameworks such as ASP.NET Core within a holistic cross-platform discourse, the article contributes a nuanced, integrative perspective that advances theoretical understanding while offering strategically relevant insights for researchers, practitioners, and decision-makers.